Thalassas: An International Journal of Marine Sciences - Thalassas: An International Journal of Marine Sciences (Springer Nature, 2026)
Thalassas is an international journal devoted to multidisciplinary studies in marine sciences. Established in 1983, the journal covers a broad range of locales, from the deep sea to coastal environments and includes papers on marine and coastal biology, chemistry, geology and physics, with a particular emphasis on multidisciplinary work.
FI 0.26
Q4
Keywords: Earth; Space & Environmental Sciences; Earth Sciences; Ciencias de la Tierra; Acuerdos transformativos; Transformative agreements; Biología marina y costera; Biología química; Geología; Física; Multidisciplinaria